On the subject of rural education: multi-séries teaching and pedagogical nucleation in Santa Cecília - PB - Robson de Arruda; Robéria Nádia Araújo Nascimento (Universidade Federal do Norte do Tocantins, 2020)
This article weave considerations rural education and addresses pedagogical aspects of teaching in multi-séries classes. It analyzes the testimonies of five teachers and a pedagogical technician who participated in the process of nucleating classes and schools in the city of Santa Cecília - PB. Dialogue with Arroyo and Fernandes (1999), Baptista (2003), Carvalho, Robaert and Freitas (2015), Ramalho (2008), Tardif (2014), Pimenta (2012), among others, in order to understand the stereotype of the field as a place of delay in through educational policies whose references are serial education and urban schools. The observation made showed that there was a new meaning of teaching practice and student learning in schools submitted to the process of serialization.